Archival Suspicion and Authorial Desire in The Dalkey Archive - Gülden Hatipoğlu (Ideas: Journal of English Literary Studies, 2023)
The central aim of this article is to explore the politics of the archive and archival mnemonics in Flann O’Brien’s last novel, The Dalkey Archive (1964). The argumentative axis moves along the relation between archival power and authorial agency, especially in terms of re/imagining alternative histories/archives. Relying on the metaphor of the book as an archive, and the author as an archivist, the article introduces a reading of the novel within the historical context of Ireland’s post-independence intellectual and political climate. O’Brien’s biting dark humour, which exposes the ideological fictionality of archival constructs and debunks canonical authority, is shown to introduce a critical commentary on many aspects of the relationship between authorship and power.